Growth of ZnS Thin Films using Chemical Spray Pyrolysis Technique. (2019) - Al-Diabat, A.M.; Ahmed, N.M.; Hashim, M.R.; Almessiere, M.A.
Abstract: It is well acknowledged that thin films of zinc sulfide (ZnS) can be successfully synthesised via spray pyrolysis of an aqueous solution of zinc acetate and thiourea onto a glass substrate at a temperature of 200°C. However, the effect of spray rate on the structural and optical properties of ZnS thin films has not been considered deeply. Therefore, this study synthesized ZnS thin films on glass substrates under different spray rate (1, 2, 3 and 4 mlmin -1 ). The films were characterized using X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), UV-Vis-NIR spectrometry, and photoluminescence (PL) spectroscopy. The X-ray diffraction of all the samples confirmed the characteristic cubic structure of ZnS thin films. On the other hand, the morphology and crystallinity seemed to be depended on the spray rate. It was found that the value of bandgap of ZnS films slightly increased when the spray rate was increased. Furthermore, the variations observed in the 3.35–3.80 eV range are most likely related to the Zn (S, O) formation within the solid solution. PL analysis specified the presence three peaks (2.38, 2.98 and 3.5 eV) at spray rate of 3 ml min-1, which are attributable to Zn vacancies, S vacancies, interstitial sulfur and interstitial zinc.